New empirical correlations for sizing adiabatic capillary tubes in refrigeration systems - Aahar, A. A. (2011)
This paper presents new empirical correlations that have been developed for sizing adiabatic capillary tubes used in small vapor compression refrigeration and air-conditioning systems. A numerical model which is based on the basic equations of conservation of mass, momentum and energy was developed. Colebrook's formulation was used to determine the single phase friction factor. The two-phase viscosity models - Cicchitti et al., Dukler et al. and McAdam et al. were used based on the recommendation from literature to determine the two-phase viscosity factor. The developed numerical model was validated using the experimental data from literature. The numerical model was used to study the effects of relevant parameters on capillary tube length and the results showed that the length of capillary tube increase with increase in condensing temperature, subcooling, and inner diameter of tube but decrease with increase in surface roughness and mass flow rate. Thereafter, empirical correlation of the capillary tube length with the five dependent variables was presented. The empirical models are validated using experimental data from literature. Different from the previous studies, the empirical models have a large set of refrigerants and wide operating conditions. The developed correlation can be used as an effective tool for sizing adiabatic capillary tube with system models working with alternative refrigerants.